First report of Cladosporium cladosporioides causing leaf blight on Sambucus chinensis in China - Cui, Qunyao; Lyu, Hui; He, Ling; Chi, Meifeng; Wang, Wentao; Xie, Chengjian; Zhang, Bingchuan; Zhou, Cao; Xu, Shan (Plant disease, 2023)
Sambucus chinensis, belonging to the Caprifoliaceae family, is an economically large herb plant that is widely cultivated in southern China for its good ornamental characteristics, edible properties, and medicinal values. In July 2021, symptoms of leaf spot were observed on Sambucus chinensis plants in two fields of Chongqing Medicinal Botanical Garden (29º8'26" N, 107º13'23" E) in Nanchuan city, Chongqing, China. Disease incidence was approximately 35 and 50% for each field. The symptoms were initially yellow or black irregular spots on leaves, and then increased to larger dark brown lesions. Finally, the entire infected leaf was blighted, withering, curl and abscission. Ten blight leaves were randomly sampled from fields. Tissues were cut into small pieces and surface sterilized with 75% ethanol for 30 s and sterilized in 2% sodium hypochlorite for 2 min, rinsed thrice with sterile distilled water, plated on potato dextrose agar (PDA) plates, and incubated at 25°C for 7 days in the dark. Later, 20 isolates were obtained from the infected leaves and had similar characteristics. Three isolates were randomly selected (CQ81, CQ82, CQ83) for the further study. Colonies on PDA were olive-green to brown with a velvety texture. Conidia (n=30) were pale- to olive-brown, smooth to verruculose and produced in long, branched chains which were easily disarticulate, single celled, and elliptical to limoniform, and measured as 2.51~4.29 × 1.63~2.14 μm. Conidiophores were solitary, straight or flexous, often unbranched. The DNA of three isolates were extracted and the internal transcribed spacer (ITS) region and translation elongation factor 1-alpha (TEF1-α) were sequenced using primer pairs ITS1/ITS4 (White et al. 1990) and EF1-728F/EF1-986R (Carbone and Kohn 1999), respectively. The sequences of three isolates were 100% identical, and one representative isolate CQ82 were deposited in GenBank (ON387641, ITS; and ON409522, TEF). BLASTn analysis of these sequences showed 99 to 100% nucleotide identity with the sequences of C. cladosporioides CPC 14705 in Korea (Bensch et al. 2010). Phylogenetic analysis using Neighbor-joining method and concatenated sequences (ITS +TEF1) with MEGA7 placed isolate CQ82 in C. cladosporioides with 99% bootstrap support. On the basis of morphological and molecular characteristics, the isolates were identified as C. cladosporioides (Bensch et al. 2010; Nam et al. 2015). A total of sixteen healthy potted plants of S. chinensis were conducted for the pathogenicity test. Eight plants were selected and one shoot of each plant was randomly used for inoculation. Leaves from the shoot of each plant were brushed with 106 conidia/ml suspension of isolate CQ82. Another 8 plants were performed in the same procedure, inoculated with sterile distilled water as control. All plants were covered with plastic bags for two days and then arranged in a greenhouse with 80% relative humidity at 25°C. The pathogenicity test was repeated thrice. After 15 days inoculation, the similar symptoms were observed on the inoculated leaves, whereas controls remained healthy. The pathogen was reisolated from blight tissue and identified as C. cladosporioides by the methods described above. Although this fungus was previously reported to cause leaf disease on many plants (Meneses et al. 2018; Sun et al. 2017), this is the first report of C. cladosporioides causing leaf blight on S. chinensis in China. This study will establish a foundation for controlling the disease.